The Role of Trust in Mediating the Influence of Islamic Branding on the Decision to Stay at Sharia Hotels - Wandari, Eny Lastio; Siswanto, Siswanto; Mahfudz, Masyhuri (Iqtishodia: Jurnal Ekonomi Syariah, 2025)
This study analyzes the mediating role of trust in the relationship between Islamic branding and stay decisions at sharia hotels. Although interest in Islamic-based hospitality is increasing, limited studies have explored the mediating effect of trust in this context, especially in Indonesia. Using a quantitative approach with Structural Equation Modeling (SEM-PLS), data were collected from 200 respondents who had stayed in sharia hotels in Malang City, East Java, through purposive sampling. The results show that Islamic branding positively and significantly affects trust, and trust significantly influences stay decisions. The model explains 68.5% of the variance in stay decisions (R² = 0.685), with a Variance Accounted For (VAF) of 63%, confirming partial mediation. These findings highlight that a strong Islamic brand enhances customer trust and encourages stay decisions. Theoretically, this study enriches Islamic marketing literature by validating the mediating mechanism of trust, while practically offering insights for sharia hotel managers to strengthen trust through consistent Islamic branding.